Interaction between strong sound waves and cloud droplets: Cloud chamber experiment. (May 2021) - Qiu, Jun; Tang, Li-Juan; Cheng, Liang; Wang, Guang-Qian; Li, Fang-Fang
Highlights: Cloud chamber experiments to study sound wave action on cloud droplet agglomeration. Obtained direct evidence of acoustic agglomeration of cloud droplets. At 35–100 Hz, threshold sound pressure level (SPL) for agglomeration is 114–121 dB. For a fixed SPL, agglomeration effect is most notable under frequency of 50–65 Hz. At a set sound frequency, agglomeration effect is more significant under higher SPL. Abstract: Acoustic agglomeration refers to the group effect of micro-particle groups in a strong sound field, which promotes relative motion among the particles, leading to the rapid agglomeration of the particle groups. The existing theoretical and experimental research on acoustic agglomeration is focused on solid particles such as soot particles and aerosols, and the acoustic agglomeration of micron-scale cloud droplets has not been intensively investigated. In this study, a cloud with an average particle size of 10 μm is generated in a cloud chamber at room temperature, and a series of acoustic agglomeration experiments of cloud droplets under the action of sound waves with a frequency and sound pressure level (SPL) of 35–100 Hz and 112–122 dB, respectively, are conducted to examine the impact law of the sound waves with different frequencies and SPLs on the cloud droplet size spectrum. At a constant sound frequency, the agglomeration effect of the cloud droplets is more pronounced under the action of sound waves with a higher SPL. Under a constant SPL, the agglomeration effect is the most notable when the sound frequency ranges from 50 to 65 Hz. The threshold SPL for the effective agglomeration ranges from 114 to 121 dB when the sound frequency is 35–100 Hz, and the threshold SPL gradually increases with the sound frequency. The findings can clarify the effect of the sound waves in promoting cloud condensation and provide guidance to develop atmospheric intervention technologies based on strong sound waves.